Penjadwalan Dokter dan Perawat IGD Menggunakan Algoritma Kunang-Kunang - Hulliyatul Khoiriyyah; Khusnul Novianingsih; Al Azhary Masta Masta (Department of Mathematics, Hasanuddin University, 2024)
The Emergency Room (ER) is a part of the hospital responsible for providing initial treatment to patients with life-threatening conditions. The operational hours of the ER follow the schedule set by the hospital. ER must be ready to serve emergency patients 24 hours a day and 7 days a week. Therefore, the scheduling of doctors and nurses in the ER needs to be well-managed to enhance the efficiency of doctors and nurses in responding emergency patients quickly and effectively. In this study, the problem of doctors and nurses scheduling in the ER is solved using the Firefly Algorithm, in which doctors and nurses represented as fireflies. This algorithm is chosen since its ability to find optimal solutions for complex optimization problems. In this research, doctors and nurses can submit schedule requests to improve job satisfaction. The optimization model is constructed by a number of constraints including the availability of doctors and nurses, schedule requests, and the operational needs of the ER. The Firefly Algorithm is applied to find the optimal solution for the model. Simulation results show that this algorithm can produce an optimal schedule, in which 70.6% of doctors' schedule requests and 98.2% of nurses' schedule requests are being fulfilled.